Crystallography - Akitsu, Takashiro (IntechOpen, 2019)
This book reviews both current research in and several principles of crystallography, not only for natural sciences, mathematics, physics, chemistry, biology, and earth sciences but also for applied engineering such as material and medical or pharmaceutical sciences. As a review book on crystallography, this book will help with theoretical considerations and understanding the basic theory of frontier experiments, among other topics.